Assessing Training Methods to Educate Dairy Workers - L. Mendonca; B. E. Voelz; A. Scanavez (Kansas Agricultural Experiment Station Research Reports, 2016)
Training employees is fundamental for dairy producers to achieve efficiency in order to increase profitability. Training videos offered online are becoming more common and recommended to train employees. The goals of this survey were to evaluate the comfort level of dairy employees in using computers and tablets, and preferred training delivery methods. A total of 71 employees from 6 dairies were interviewed. Interviews were conducted in the preferred language of the interviewee – English or Spanish. Of the respondents, 52 and 65.6% of employees consider computers and tablets easy to use, respectively. More than half of the employees reported that they do not use computers or tablets on a regular basis. The majority of employees (70%) would rather have a training session in a face-to-face format than a computer- or tablet-based format. This survey suggests that dairy employees may not be comfortable using computers in training sessions, which may limit the utility of some specific technologies to educate employees.
Keywords: employee training; survey; technology